The level of awareness on Wasiyyah practice towards Halal Management Part 5 students in UiTM Puncak Alam / Munirah Zahril - Zahril, Munirah (2020)
This research is to investigate the awareness level of Halal Management Part 5 UiTM Puncak Alam students on wasiyyah practice. Wasiyyah very important to the society and to the testator of wasiyyah itself. However, people tend to care less about wasiyyah practice in Malaysia. Wasiyyah also one of the important areas in Islamic estate planning that could affect the statistics of unclaimed assets in Malaysia. The objectives of this study are to study the concept of wasiyyah, to examine the awareness level on wasiyyah and to identify the barriers in Islamic inheritance distributions in Malaysia. The methods that used for this research are quantitative, which the researcher gave questionnaires to the students and the scope of the survey is Halal Management Part 5 students. In addition, the researcher analyses the data using Statistical Package for Social Science (SPSS) to measure the validity. The descriptive analysis and content of reading material and relevant supporting standard.